Educational Administration: Theoretical Perspectives on Practice and ResearchEducational Administration: Theoretical Perspectives on Practice and Research, by SilverPaula. New York: Harper & Row, 1983, 415 pp., $19.95 cloth. - Willey, Darrell S. (Academy of Management Review, 1984)
The article presents a review of the book ?Educational Administration: Theoretical Perspectives on Practice and Research,? by Paula Silver.